Genetic Variability for Zinc Use Efficiency in Chickpea as Influenced by Zinc Fertilization - Singh Shivay, Yashbir; Prasad, Rajendra; Pal, Madan (International Journal of Bio-resource and Stress Management, 2014)
Zinc deficiency is the major problem in chickpea production when grown on highly permeable light textured soils, low in organic matter content and continuously cropped with rice. A field experiment was conducted for two crop years (2011-12 & 2012-13) at the Indian Agricultural Research Institute, New Delhi to study the effect of variety and zinc (Zn) application on the grain yield, Zn uptake and Zn use efficiency in chickpea. In general, Pusa 372 out-performed Pusa 2024 and Pusa 5028 in growth characters, grain yield, Zn uptake and physiological efficiency of Zn applied. Chickpea variety Pusa 372 recorded 2.13 t ha-1 grain yield which was 0.71 and 7.04% higher compared to Pusa 2024 and Pusa 5028 (based on mean of 2 years). Similar results were also observed with straw yield of chickpea. From the viewpoint of Zn concentration in grain and its biofortification, Pusa 5028 appears promising especially at the highest level of Zn (7.5 kg Zn ha-1); in the second year of study it recorded the highest Zn concentration of 50.1 mg Zn kg-1 grain. Each successive increase in the application of Zn from 2.5 to 7.5 kg ha-1 also increased the grain as well as straw yields of chickpea; however the significantly highest grain yield (2.24 t ha-1, mean of 2 years) was recorded with application of 7.5 kg Zn ha-1 which was 18.52, 10.89 and 4.19% higher compared to 0, 2.5 and 5.0 kg Zn ha-1 respectively.